KAJIAN HUKUM PIDANA TERHADAP PELAKU KEJAHATAN SEBAGAI PEMILIK NARKOTIKA GOLONGAN I (STUDI PUTUSAN NOMOR:463/Pid.Sus/2024/PN MDN) - Prayuri, Shalsya Savira; Zulyadi, Rizkan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this research is solely to focus on discussing the form of legal regulation concerning offenders who possess Category I narcotics and the judges’ considerations in imposing criminal sanctions on such offenders, based on Decision Number: 463/Pid.Sus/2024/PN Mdn. The research method applied is normative legal research, which relies on secondary data. Data collection techniques include literature study from books, journal articles, and field studies by obtaining court decision data, followed by qualitative analysis. The findings indicate that the legal regulation of offenders who possess Category I narcotics is stipulated under Law Number 35 of 2009 concerning Narcotics, particularly in Articles 111 to 119, which cover narcotics abusers, distributors, and sellers who own narcotics. The judge’s consideration in imposing criminal sanctions was based on the facts established during the trial, where it was proven that the defendant was in possession of Category I narcotics in the form of methamphetamine, as evidenced by the Forensic Laboratory Examination Report Number: 334/NNF/2023 dated January 29, 2024, issued by the North Sumatra Regional Police. The Panel of Judges further provided specific considerations by sentencing the defendant to imprisonment for 7 (seven) years and 6 (six) months, taking into account both aggravating and mitigating circumstances relevant to the defendant. Keywords: Offender, Crime, Owner of Category I Narcotics